2020
DOI: 10.3390/cells9102166
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-2 and Calcium Handling: Molecules, Organelles, Cells and Brain Networks

Abstract: Presenilin-2 (PS2) is one of the three proteins that are dominantly mutated in familial Alzheimer’s disease (FAD). It forms the catalytic core of the γ-secretase complex—a function shared with its homolog presenilin-1 (PS1)—the enzyme ultimately responsible of amyloid-β (Aβ) formation. Besides its enzymatic activity, PS2 is a multifunctional protein, being specifically involved, independently of γ-secretase activity, in the modulation of several cellular processes, such as Ca2+ signalling, mitochondrial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 171 publications
(244 reference statements)
1
22
0
Order By: Relevance
“…In this Special Issue in Cells , six reviews address the newest results and advances in calcium signalling deregulation mechanisms in AD, how they are linked to other molecular players involved in AD pathogenesis, and the potential therapeutic approaches to correct calcium alterations to treat AD [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In this Special Issue in Cells , six reviews address the newest results and advances in calcium signalling deregulation mechanisms in AD, how they are linked to other molecular players involved in AD pathogenesis, and the potential therapeutic approaches to correct calcium alterations to treat AD [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
mentioning
confidence: 99%
“…Our review [ 23 ] and that by John McDaid et al [ 26 ] extensively highlight the role of PS1 in controlling several aspects of the subcellular calcium signalling deregulation and in synaptic plasticity. The review by Paola Pizzo et al [ 28 ] specifically focuses on the role of PS2 in the modulation of ER and Golgi apparatus calcium handling, calcium entry through the plasma membrane channels, mitochondrial function, ER–mitochondria communication, and autophagy. The authors overview the alterations of calcium homeostasis observed in several cell lines expressing FAD-PS2 mutants, in human-derived fibroblasts, and in PS2 mice and ex vivo models (primary neurons culture and acute hippocampal slices) [ 28 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cytosolic Ca 2+ Handling in PS2-/-Neurons Cytosolic Ca 2+ responses were evaluated in primary cortical neuronal cultures from WT and PS2-/-newborn mice. Since PS1 and PS2 can have differential effects on cell Ca 2+ handling (revised in [30]), and a coregulation of PS1 and PS2 expressions has been previously reported [5,31], we firstly assessed PS1 expression level in WT and PS2-/cortical neurons finding a slight increase, although nonsignificant, in this protein in the absence of PS2 (Figure S1A).…”
Section: Ca 2+mentioning
confidence: 99%